Thyroid-sparing volume-modulated arc therapy in patients with non-distant metastatic nasopharyngeal carcinoma: a feasibility study - Xie, Renxian; Lu, Jiayang; Cai, Qingxin; Li, Longbo; Xie, Keyan; Chen, Tong; Huang, Hongxin; Chen, Jianzhou; Zhang, Ying; Chen, Chuangzhen (Frontiers in Oncology, 2025)
PurposeTo assess the dosimetric feasibility of thyroid-sparing volume-modulated arc therapy (TS VMAT) in patients with non-distant metastatic nasopharyngeal carcinoma.MethodsTS VMAT plans and non-thyroid-sparing volume-modulated arc therapy (NTS VMAT) plans were created using inverse-planning VMAT and computed tomography datasets of 60 patients from two centers using the Eclipse version 15.6 treatment planning system. These patients were split up into three groups, each consisting of ten patients: the bilateral upper neck irradiation group, the one-side lower neck irradiation group, and the bilateral lower neck irradiation group. Dose volume histograms, the homogeneity index (HI), conformity index (CI), and irradiation doses to the thyroid and other OARs were used to assess the two treatment plans.ResultsThere were no statistically significant differences in HI, CI, and dosage distribution to OARs between the two plans, except for the bilateral lower neck irradiation group, where mild but clinically acceptable differences were observed. Surprisingly, the TS VMAT plans significantly reduced the radiation dose to the thyroid gland across all three groups without compromising target coverage, conformity, or dose homogeneity. Specifically, the mean dose to the thyroid was substantially lower in the TS VMAT plans compared to the NTS VMAT plans. Additionally, the volume of the thyroid irradiated with 40 Gy or more was also significantly reduced in the TS VMAT plans.ConclusionsThe TS VMAT plan is appropriate for radiotherapy planning in patients with non-distant metastatic nasopharyngeal carcinoma. The TS VMAT plan reduces radiation dosage to the thyroid gland compared to the NTS VMAT plan, lowering the risk of hypothyroidism without exacerbating the HI, CI, and the irradiation doses to OARs.